Effects, but no interactions, of ubiquitous pesticide and parasite stressors on honey bee (Apis mellifera) lifespan and behaviour in a colony environment. (15th April 2015) - Retschnig, Gina; Williams, Geoffrey R.; Odemer, Richard; Boltin, Janina; Di Poto, Cornelia; Mehmann, Marion M.; Retschnig, Peter; Winiger, Pius; Rosenkranz, Peter; Neumann, Peter
Summary: Interactions between pesticides and parasites are believed to be responsible for increased mortality of honey bee ( A pis mellifera ) colonies in the northern hemisphere. Previous efforts have employed experimental approaches using small groups under laboratory conditions to investigate influence of these stressors on honey bee physiology and behaviour, although both the colony level and field conditions play a key role for eusocial honey bees. Here, we challenged honey bee workers under in vivo colony conditions with sublethal doses of the neonicotinoid thiacloprid, the miticide tau‐fluvalinate and the endoparasite N osema ceranae, to investigate potential effects on longevity and behaviour using observation hives. In contrast to previous laboratory studies, our results do not suggest interactions among stressors, but rather lone effects of pesticides and the parasite on mortality and behaviour, respectively. These effects appear to be weak due to different outcomes at the two study sites, thereby suggesting that the role of thiacloprid, tau‐fluvalinate and N . ceranae and interactions among them may have been overemphasized. In the future, investigations into the effects of honey bee stressors should prioritize the use of colonies maintained under a variety of environmental conditions in order to obtain more biologically relevant data.